ENRICHING VOCABULARY SIZE OF EFL LEARNERS THROUGH DELIBERATE VOCABULARY LEARNING - Sariani Sariani; Witri Handayani; Mutia El- Khairat (Universitas Negeri Padang, 2016)
This research is a quantitative study which aims to enhance the speaking fluency of English Department’ students, State Polytechnic of Padang (PNP) through vocabulary deliberate learning. It was established by implementing linked word’s game as one of ways to enrich the student’s vocabulary size. The data was taken from the fresh year students who took Speaking 1 subject. It consisted of 2 intact classes; 1A with 26 students, and 1B with 27 students. The 1A class was set as experimental group, on another hand 1B class was set as control group. The analysis compared by the score perceived on their Pre-Test by using the Vocabulary Size Test (VST) designed by Paul Nation to thescore on their Post-Test right after the treatment. The data were analyzed by using T-test for independent sample test in comparing between experiment group and control group. The result of this research displayed that control class showed that t(24) = -.834, p = .413. So, it can be concluded that no significant change in post test score compared with pre test score in control class because p>0,05. Meanwhile in experimental group t(22) = -1.937, p = 0.066. P value in experimental group closed to 0.05 which means that there was significance change from 27.13 (pre-test score) into 32.35 (post-test score). Shortly, this game influenced the enrichment of the students vocabulary size.